Crazy Rich Asians and pan-Asian screen cosmopolitanism. Issue 2 (1st August 2020) - Gallagher, Mark
Crazy Rich Asians (2018), a box-office hit in North America, provoked celebration particularly from Asian American commentators and actors. Shot in Singapore and Malaysia with an Asian and Asian American cast, it was a success too in Singapore itself and in territories such as Hong Kong, Taiwan and Australia but not in East Asia's largest markets, those of China, Japan and South Korea. Focusing on the phenomenon of Crazy Rich Asians' release, particularly its engagement with and circulation in East and Southeast Asia and its polarized reception among different Asian American and Asian communities, this article traces a series of discursive flashpoints to understand the film's position in Asian and Asian American film culture. Arguing that the fortunes of US releases with Asian and Asian American casts reveal cosmopolitanism's invisible borders, the article proposes a model of pan-Asian screen cosmopolitanism. This model recognizes that even globally hybrid screen texts such as Crazy Rich Asians bear cultural markers that may inhibit their appeal in territories with shared ethnic heritages but discrete social histories.